Adriatlas 4. Produzioni artigianali in area adriatica: manufatti, ateliers e attori (III sec. a.C. - V sec. d.C.) - RIGATO, DANIELA; MONGARDI, Manuela; VITELLI CASELLA, MATTIA (PrimaLun@, 2021)
This fourth volume of the series AdriAtlas collects the papers presented at the International Round Table held in Bologna on May 23rd -25th 2019. It contains in total 21 contributions of French, Italian, Croatian and Slovenian scholars. The reflections focus on artisanal productions in the Adriatic region with a particular attention to five themes: craftsmanship and manufacturing between city and countryside; epigraphy, crafts and society; amphora productions; production of fine and common ware; textile production. Among the purposes of the conference, we can highlight: -to shed light on the different production methods developed in geographical contexts around the Adriatic Sea, seen as a privileged ambiance for the exchange of ideas, techniques, fashions, goods, and people; -to provide an updated, albeit partial, picture of the productive phenomenon in its various forms and its interactions with the other economic players.